The Implementation of Guided Dhikr Therapy to Reduce Anxiety in Close Fractures Patients - Khoirunisak, Naretta; Hakam, Mulia; Kushariyadi; Setyowati, Sulis (Al-Hijrah Indonesia, 2024)
Patients with fracture conditions often experience complaints of excessive anxiety, where anxiety is felt due to the pain that is felt and the provision of invasive or surgical action plans. Preoperative patients will certainly feel excessive anxiety. Feelings of anxiety will cause stress and cause nursing problems, namely anxiety. Dhikr therapy is a non-pharmacological therapy and includes complementary therapy, where this therapy can reduce the level of anxiety felt by preoperative patients. The purpose of this study was to analyze the administration of dhikr therapy in patients with preoperative close fractures of the left distal radius. This research uses the case study method. This research was conducted in the Seruni room at dr. Soebandi Regional Public Hospital of Jember. Dhikr therapy is carried out for four consecutive days with a time of approximately 20 minutes. The results obtained from this study after administration of anxiety reduction combined with dhikr therapy obtained the patient's anxiety scale level from VAS-A4 to the VAS-A0 scale, visualization of anxiety complaints decreased, restless behavior decreased, and eye contact increased, respiratory rate 16 x/minute, SpO2 98%, pulse 90 x/minute, and blood pressure 130/80 mmHg. Reducing anxiety with dhikr therapy can be given to pre-surgery patients, this can improve health quality, sleep quality, and physical condition.